PENGARUH PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP SELF CARE MANAJEMENT PADA PENDERITA HIPERTENSI DENGAN PENDEKATAN TEORI DOREOTHEA E OREM - Pramadaningati, Ike; Nurbadriyah, Wiwit Dwi; Fikriana, Riza (Universitas Harapan Bangsa Purwokerto, 2021)
Self care management in patients with hypertension is an individual's ability to carry out self-activities to maintain life, improve and maintain health for individual well-being to avoid complications. The purpose of this study was to analyze the effect of knowledge and family support on Self-care Management in Hypertensive Patients with Dhorothea E Orem Theory Approach. This type of research is a quantitative study, using andesign analytical descriptive with aapproach cross-sectional. Samples were taken using a purposive sampling technique in the elderly posyandu in Pamotan Village as many as 65 respondents. Data collection was done by distributing questionnaires to respondents. The statistical test used is multiple linear regression analysis test. The results show that there is an influence on the knowledge variable with a p-value 0.004 and a regression coefficient of 1.051, and there is an influence on thesupport variable familywith a p-value of 0.007 and a regression coefficient value of 0.248. Based on these statistical results, it was concluded that the variables of knowledge and family support had an effect on self-care management in patients with hypertension.